2017
DOI: 10.1177/1359105317739966
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of self-esteem on the relationship of living environment, anxiety, and depression of underprivileged children: A path analysis in Chinese context

Abstract: This study aimed to explore the relationships of living environment, self-esteem, anxiety, and depression of children in poverty. A sample of 1314 children (grades 4-9) was collected by a school-based survey in Xiushui city, Mainland China. Structural equation modeling was adopted to analyze the data and verify the hypothesized model. Results showed that living environment was negatively correlated with poor children's anxiety and depression levels, and self-esteem had a mediating effect on the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…People with high self-esteem are generally believed to have sufficient internal resources of confidence and positive emotions to cope with external threats (Steele, 1988). High self-esteem is also considered to be a buffer against negative experiences, protecting children and adolescents from trauma-related stress (Moksnes et al, 2010; Yin et al, 2017). This also seems to be true for survivors of natural disasters such as earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…People with high self-esteem are generally believed to have sufficient internal resources of confidence and positive emotions to cope with external threats (Steele, 1988). High self-esteem is also considered to be a buffer against negative experiences, protecting children and adolescents from trauma-related stress (Moksnes et al, 2010; Yin et al, 2017). This also seems to be true for survivors of natural disasters such as earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Parental absence, as a consequence of parents’ rural-to-urban migrations, often has substantial detrimental effects on children’s depression (He et al, 2012; Wu et al, 2015; Yin et al, 2017). In recent years, many studies have reported high prevalence rates of depression among left-behind children in China (Cheng and Sun, 2015; He et al, 2012; Wu et al, 2015) and demonstrated that left-behind children were at greater risk for developing depression than non-left-behind children (Liang et al, 2017; Wang et al, 2015; Wu et al, 2015; Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that in low-income families, parents typically exhibit negative parenting behaviors, including inadequate parental involvement [26,27], which in turn is detrimental to children's development [28]. In contrast, positive parental involvement can alleviate depressive symptoms and reduce the risk of depression in children [9]. In addition, parental involvement longitudinally predicts the development of children.…”
Section: The Chain Mediating Effect Of Parental Involvement and Child...mentioning
confidence: 99%
“…According to the report published by the Ministry of Civil Affairs of China, the divorce rate rose from 2.0% in 2010 to 3.4% in 2019 [41,42], which has led to increase in the number of children raised in single-parent families. Compared with intact families, children from single-parent families face more physical and mental health problems [15], including fewer positive psychological states [43], a higher risk of depression [9,44], and lower self-esteem [45]. These negative outcomes also continue into adulthood [46].…”
Section: Differences Between the Single-parent Family And The Intact ...mentioning
confidence: 99%
See 1 more Smart Citation